Sosialisasi Siaga Bencana Dan Simulasi Bantuan Hidup Dasar (BHD) Pada Masyarakat Di Desa Ngkeran Kecamatan Lawe Alas Aceh Tenggara - Ultra Madani; Sri Wahyuni Sambo (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Disasters contain three basic aspects, namely: the occurrence of a threatening and destructive event or disturbance, the event or disturbance threatens the life, livelihood, and function of the community, and the threat results in victims and exceeds the community's ability to cope with their resources. Community Service Activities (PKM) Socialization of Disaster Preparedness and Simulation of Basic Life Support (BHD) in the Community in Ngkeran Village, Lawe Alas District, Southeast Aceh, was held on February 7-8 2024 with a total of 45 participants. socialization was provided by the community service team regarding checking response and emergency medical services, checking pulse, carrying out early CPR, and early defibrillation with AED. The extension participants seemed enthusiastic about the materials presented by the resource persons and were able to be actively involved, so this extension activity took place in a two-way system and many participants asked questions. The presentation of the extension material was followed by discussion, ice-breaking, and distribution of door prizes to participants who were active during the discussion activities.